Juridical Review of the Implementation of Marriage Legalization Applications - Rahmat, Doris; Ash-Shidiqqi, Ellectrananda Anugerah; Akhmad Faisol, Syahid; Lumban Gaol, Indra Devian (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
Marriage legalization (iṣbat nikah) is a legal mechanism submitted to the Religious Court to obtain official recognition of a marriage conducted according to Islamic law but not yet officially recorded in state administration. This study aims to examine the juridical basis, implementation procedures, and obstacles in submitting an iṣbat nikah application at the Karanganyar Regency Religious Court. The method used is normative juridical research with a statutory and case study approach. The study results indicate that the legal basis for iṣbat nikah is regulated in Article 7, paragraph (3) of the Compilation of Islamic Law (KHI), Law Number 1 of 1974 concerning Marriage, and Law Number 50 of 2009 concerning the Second Amendment to Law Number 7 of 1989 on Religious Courts. The practice at the Karanganyar Religious Court shows an increase in the number of applications, especially from couples in unregistered marriages (nikah siri). The main obstacles in the implementation are the lack of public legal awareness and limitations in evidence.This research concludes the need to improve public legal literacy as well as the active role of village government officials in encouraging early marriage registration.